Synthesis and Characterization of Imide Containing Hybrid Epoxy Resin with Improved Mechanical and Thermal Properties - U. G. Rane; A. A. Sabnis; V. V. Shertukde (International Journal of Polymer Science)
Phosphorous containing amine, tripropyldiamine phosphine oxide (TPDAP), and hybrid monomer 4-(N-phthalimidophenyl) glycidylether (PPGE) were synthesized and characterized by Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, and elemental analysis (EDX). PPGE was incorporated in bisphenol A epoxy resin (BPA) in various concentrations (5% to 20%), based on a weight percentage of BPA resin. Curing was carried out with the stoichiometric amount of TPDAP and 1,3-propanediamine (PDA) to result in cross-link network. Various mechanical, chemical, thermal, and flame retardant properties of modified and unmodified epoxy resin were studied. The coatings obtained with the addition of PPGE were found to have improved properties as compared with those of the unmodified resin. Coatings with 15% loading of PPGE showed improved flame retardant and mechanical properties with stable thermal behaviour.